GROWTH PERFORMANCE OF SILVER BARB, PUNTIUS GONIONOTUS WITH MAJOR CARPS UNDER POLYCULTURE - M.SABAT; N.K.SIAL; G.C.KUND; S.NANDA (The Bioscan, 2020)
The present investigation was carried out to study the growth performance of silver barb, Puntius gonionotus with Indian major carps under polyculture system. Uniform sized fingerlings of silver barb and carps were stocked in cement cisterns at a rate of 10,000 numbers of fingerlings/ha for a period of 150 days. The treatments comprised of T 0 with catla, rohu, mrigal and common carp stocked at a ratio of 3:4:1:2, T 1 with catla, rohu, mrigal, common carp and silver barb at a ratio of 3:3:1:2:1, T 2 with catla, rohu, mrigal, common carp and silver barb at a ratio of 3:2:1:2:2, T 3 with catla, rohu, mrigal, common carp, and silver barb at a ratio of 3:1:1:2:3. The average weight gain by silver barb in T 1 , T 2 and T 3 were recorded to be 43.34±0.73 g, 55.65±1.16 g, 88.41±0.68 g whereas among carps, the catla recorded highest weight gain (93.14±1.52 g) followed by common carp (74.79±1.33 g), mrigal (66.19±0.93 g) and rohu (53.38±1.01 g). The analysis of data indicates a significant difference (p<0.05) between the treatment T 3 and T 0 which further strengthens the fact that polyculture of silver barb with four species of carps is beneficial in terms of enhancing the yield from the polyculture system.